2020
DOI: 10.3390/ijerph17186621
|View full text |Cite
|
Sign up to set email alerts
|

Urban Noise and Psychological Distress: A Systematic Review

Abstract: Chronic exposure to urban noise is harmful for auditory perception, cardiovascular, gastrointestinal and nervous systems, while also causing psychological annoyance. Around 25% of the EU population experience a deterioration in the quality of life due to annoyance and about 5–15% suffer from sleep disorders, with many disability-adjusted life years (DALYs) lost annually. This systematic review highlights the main sources of urban noise, the relevant principal clinical disorders and the most effected countries.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 99 publications
0
12
0
1
Order By: Relevance
“…These findings hold, as in the present study, when adjusting for demographic, socioeconomic, and health controls (Sass et al, 2017). A recent systematic review (Mucci et al, 2020) indicated that chronic exposure to noise is harmful for both physical and mental health, particularly for auditory perception, cardiovascular and gastrointestinal function, and psychological annoyance. Noise exposure also causes sleep disturbances (Kim et al, 2012; Sygna et al, 2014), with mental health consequences (Sygna et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…These findings hold, as in the present study, when adjusting for demographic, socioeconomic, and health controls (Sass et al, 2017). A recent systematic review (Mucci et al, 2020) indicated that chronic exposure to noise is harmful for both physical and mental health, particularly for auditory perception, cardiovascular and gastrointestinal function, and psychological annoyance. Noise exposure also causes sleep disturbances (Kim et al, 2012; Sygna et al, 2014), with mental health consequences (Sygna et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…No Brasil, um levantamento nacional constatou que o impacto da educação na ocorrência de depressão varia de acordo com o nível educacional alcançado pelo indivíduo, indicando que o acesso a níveis mais elevados de educação está associado a um menor risco de desenvolver depressão (Santos;.A relação entre não ter um companheiro e uma No presente estudo, foi verificado que viver na área urbana foi associado a maior prevalência de transtornos mentais. A vida urbana frequentemente se associa a um aumento nos estímulos sensoriais e a níveis elevados de estresse, decorrentes da alta densidade populacional, tráfego intenso, poluição sonora e visual, e a constante exposição a outros elementos sensoriais estimulantes (como luzes brilhantes, sons altos, movimento constante, entre outros elementos presentes no ambiente urbano que causam uma carga significativa nos sentidos e na percepção das pessoas) (Cai et al, 2021;Mucci et al, 2020). Esses fatores podem diminuir as interações sociais significativas, contribuindo para problemas de saúde mental, como depressão e solidão.…”
Section: Discussionunclassified
“…We identified papers through searches of four databases, manual searches of relevant conference proceedings, referrals from colleagues, and review of papers identified in systematic reviews examining the mental health effects of noise exposure [ 2 , 11 , 12 , 23 , 24 , 25 ]. see Appendix A Table A1 shows the full list of conferences and search terms used to scan proceedings.…”
Section: Methodsmentioning
confidence: 99%